Performance Prediction of a CSP Plant Integrated with Cooling Production. (August 2015) - Perdichizzi, A.; Barigozzi, G.; Franchini, G.; Ravelli, S.
Abstract: The integration of a Concentrated Solar Power (CSP) plant with cooling energy production is investigated in the present paper. The power block is based on a steam Rankine cycle fully driven by two types of solar concentration devices: i) Parabolic Trough Collector (PTC) solar field and ii) Heliostat field with Central Receiver (HCR). Storage tanks allow the plant to operate also during nighttime hours. Cooling production is carried out by steam-driven double-effect absorption chillers feeding a district cooling network. The system was designed to operate in "island mode" to cover both the electrical and the cooling demand for a town of about 50, 000 inhabitants. A typical location in the desert region of the Saudi Arabia Kingdom was selected as a case study. Commercial software and in-house computer codes were combined together to predict annual CSP plant performance. Results of annual plant operation on a one hour basis are presented and discussed. CSP plant showed a good capability of load-following operation, providing at the same time a relevant fossil fuel saving.